PENGARUH LAYANAN BIMBINGAN KELOMPOK TERHADAP PENINGKATAN KETERAMPILAN KOMUNIKASI INTERPERSONAL SISWA DALAM PEER GROUP DI KELAS X AK SMK MUHAMMADIYAH 2 PEKANBARU - Nurafni Eka Safitri Eka Safitri; Zulfan Saam Saam; Raja Arlizon Arlizon (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract : The tittle of this research is the effect of guidance group services towards the improvement of students interpersonal communication skill in peer group. The aims of this study were : 1) To know students’ interpersonal communication skill in peer group before implementating guidance group services, 2) To know the process of guidance group services towards the improvement of students interpersonal communication skill in peer group, 3) To know students’ interpersonal communication skill in peer group after implementating guidance group services, 4) To know the difference of students interpersonal communication skill in peer group before and after implementating guidance group services, 5) To know the effect of guidance group services towards the improvement of students interpersonal communication skill in peer group. This research used quasi-experiment method by one group pretest-posttest is applied. The subject of this research was thirty students’ of class X AK SMK Muhammadiyah 2 Pekanbaru which have low interpersonal communication skill. This research used purposive sampling technique. Based on the result of data processing, the interpersonal communication skill before implementating of guidance group services are mostly in the middle category and less in low category, whereas after implementating guidance group services are mostly in high category and less in middle category. From the calculation of t-test, tgreater than ttable (10,6 > 2,00) then the hypothesis is accepted. There is a significant difference of students’ interpersonal communication skill in peer group before and after implementating guidance group services at the level of 5% error. Based on the calculation of correlation coefficients and determinant coefficient, then the contribution of guidance group services towards students’ interpersonal communication skill amount to 37% while 63% influenced by other factors. Key words : Guidance group, interpersonal communication